Elevated serum amylase concentrations are associated with worse in-hospital outcomes among patients with acute myocardial infarction - Marijana Mikacic; Marko Kumric; Iva Rancic Vidic; Duska Glavas; Tina Ticinovic Kurir; Josko Bozic; Josip Andelo Borovac (BMC Cardiovascular Disorders)
Abstract Background In light of the well-established connection between sympathetic overactivity and early adverse events in myocardial infarction (MI) patients, this study aims to explore the potential association between serum amylase levels and in-hospital outcomes in patients with acute MI. Methods Patients aged ≥ 18 years that were hospitalized due to acute MI were prospectively included in the present study. All patients underwent clinical and laboratory examination, transthoracic echocardiography and were referred for invasive cardiology work-up as needed. Blood sample for serum amylase measurement were obtained at the time of admission, using the spectrophotometric method. A composite outcome, comprising death, ventricular tachycardia, 3rd degree atrioventricular block, instances requiring cardiopulmonary resuscitation, and transfer for cardiac surgery, was formulated for the present analysis and was the principal outcome of interest. Results A total of 202 patients were included in the present analysis. Patients who met the composite outcome exhibited significantly higher serum amylase levels than the counterparts who have not (55 (41–75) U/L vs. 87 (53–122) U/L, p < 0.001). Multivariate analysis revealed that amylase levels predicted the composite outcome independent of age, sex, acute MI type, serum creatinine, and cardiac troponin (adjusted odds ratio [aOR] 1.021, 95% confidence interval [CI] 1.008–1.034, p = 0.001). Additionally, a weak but significant association was observed between serum amylase levels and GRACE score (r = 0.25, p < 0.001). Conclusion The findings suggest that serum amylase concentration at admission might be used as a simple, non-invasive indicator of increased sympathetic activity and adverse in-hospital outcomes in patients with acute MI.